Relationship Analysis of Employee Human Resources Quality and National Achievement Center Service Performance in the Era of Industrial Revolution 4.0 - Topanal Gustiranda; Tatan Sukwika; Harsono Hadisumarjo (Ilomata International Journal of Management, 2023)
As a company, Puspresnas always works to give the Minister of Education, Culture, Research, and Technology the best advice and technical support possible. The achievement of exceptional and maximum service to students and educational institutions throughout Indonesia is the Puspresnas' vision for the future. Human resources that can adapt and are proficient in using technology in the workplace are needed in the age of the fourth industrial revolution. This study attempts to examine the relationship between employee service performance in terms of competence, adaptation, and skills. This study employs a quantitative methodology and questionnaires to collect data from Puspresnas personnel. According to the findings, the coefficient value for the constant is not significant, and the constant values for the Competence, Adaptation, and Skills variables are, respectively, 0.416, 0.354, and 0.224. The three independent factors have a positive effect on employee service performance, as shown by the regression equation for service performance above. According to the study's findings, enhancing competence, adaptability, and abilities can improve employee service performance. According to the study's findings, employees' competence, adaptability, and talents were highly correlated with how well they provided customer service at Puspresnas during the Industrial Revolution 4.0. Employees must get recurrent training as we transition to an entirely digital era so they can keep up with the ever-increasing pace of technological advancement.